Efeito do ultra-som pulsado de baixa intensidade sobre fêmur de ratas ovariectomizadas - Albertin, Lucélia Maria (2007)
Osteoporosis is a metabolic disease characterized by the damage of the bone strength due to the integration of bone density, expressed by the quantity of mineral material by bone area and volume, and the bone quality related to bone architecture, remodeling and mineralization. It is a disease that induces bone fragility and fracture spinal column and in the femur, where trabecular bone are predominant. The osteoporotic fractures are responsible by great morbidity and mortality, therefore representing a great public health problem. Studies with alternative non pharmacological treatments have been proposed and one of them is the pulsed ultrasound with low intensity (US). It is well known its osteogenic effect as a mechanical stimulus in isolates cells and bone fractures. However, these effects are not completely explained in the osteoporosis. Also, studies with aim to avoid the osteopenia with mechanical stimulus as US are rare. Therefore, the present study had the objective to analyze the effect of US (30 mw/cm2 SATA, 200µs pulse width, 1 KHz of frequency of repetition and frequency of 1.5 MHz) in femur of rats. The ovariectomized Wistar rats were used as animal model of experimental osteoporosis. Biomechanical, physical and histomorphometric parameters were analyzed. The treatment began 24h after ovariectomy, 5 days/week, during 8 weeks. Female rats with 4 months of age were divides in 6 experimental groups: US 30 and US 20 - OVX rats US stimulated during 30 and 20 minutes; Sham 30 and Sham 20 OVX rats US sham stimulated; Intact 30 and Intact20 intact rats US sham stimulated. The efficacy of the osteopenia model induced by ovariectomy was demonstrated by the physical, biomechanical and histomorphometric parameters. These parameters also showed that US was not efficiency to avoid the bone microarchiteture deterioration induced by castration.